2022
DOI: 10.3389/fmed.2022.815660
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review protocol for assessing equity in clinical practice guidelines for traumatic brain injury and homelessness

Abstract: BackgroundWhen used optimally, clinical practice guidelines (CPGs) can reduce inappropriate variations in practice, improve application of research to practice, and enhance the quality of healthcare. However, a common criticism, despite its potential, is the lack of consideration for equity and disadvantaged populations.ObjectivesThis protocol is for a systematic review of CPGs for traumatic brain injury (TBI) and homelessness that aims to assess (1) the extent to which evidence regarding TBI and homelessness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The protocol for this systematic review was published in a peer-reviewed journal. 14 To further increase replicability and transparency, we utilised a rigorous search strategy using validated search filters for CPGs 15 and methodological guides to grey literature searching. 20 In particular, the search for grey literature, is an important strength of this review, given the low precision of searching databases for peer-reviewed CPGs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The protocol for this systematic review was published in a peer-reviewed journal. 14 To further increase replicability and transparency, we utilised a rigorous search strategy using validated search filters for CPGs 15 and methodological guides to grey literature searching. 20 In particular, the search for grey literature, is an important strength of this review, given the low precision of searching databases for peer-reviewed CPGs.…”
Section: Discussionmentioning
confidence: 99%
“…We followed the screening process outlined in our protocol. 14 For the search conducted in November 2021, the resulting agreement for title and abstract screening was 94.6% for English articles and 90.0% for non-English language articles. The resulting agreement for full-text screening was 95.4% for English articles and 94.9% for non-English language articles.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…Policy guidance regarding the health of people experiencing homelessness, is clear that identification of brain injury, and management of its sequelae should be priority areas in inclusion health efforts [2,18]. Despite this, a recent review looking at clinical practice guidelines for management of brain injury, found a majority of guidelines did not have any special provision for management of brain injury in people who are experiencing homelessness [22]. This study took advantage of the unique access to a local specialist 'access' primary care provider, specialising in people experiencing homelessness and vulnerably housed people, and a local 'in reach' inclusion health service which had a presence in local acute hospitals.…”
Section: Introductionmentioning
confidence: 99%